Critical interfaith pedagogy: pro & contra - Duoblienė, Lilija (Religija ir kultūra, 2008)
The article deals with the problem of religious education in the world and Lithuania from the critical pedagogy perspective. Firstly the situation of religious education in other states is analyzed, emphasizing new approach on religious education and it’s relation with religion education. Some suggestions to transform religious education in correspondence to the new approach of contemporary philosophers (Derrida, Gadamer, Vattimo) and critical pedagogues (McLaren, Giroux, Kincheloe, Apple), basing their view on critical theory, are introduced. Special interest is shown to critical pedagogy approach to transform religious education into interfaith critical education. Such suggestion and possibility to realize it is interpreted in the broadest context of different world organizations of religious / religion education and their strategies. In this context the situation of religious education in Lithuania is describing also, trying to evaluate possibilities to change it in correspondence with the challenges of globalization.
Keywords: religious education; critical pedagogy; school curriculum; Lithuania